Reliability-based lifetime performance analysis of long-span bridges - Wu, Jun, author; Chen, Suren, 1973-, advisor; Van de Lindt, John W., committee member; Heyliger, Paul Roy, 1958-, committee member; Sakurai, Hiroshi, committee member (Colorado State University. Libraries, 2010)
Long-span bridges generally serve as the significant hub in the transportation system for normal transportation and critical evacuation paths when any disaster happens. Thus, the safety and serviceability of long-span bridges are related to huge economic cost and safety of thousands of lives. The objective of this research is to establish a general framework to evaluate the lifetime performance of long-span bridges through taking account of more realistic load situations, such as traffic flow and wind environment. After some background information is introduced in Chapter 1, Chapter 2 covers the modeling of stochastic traffic flow for the bridge infrastructure system in a more realistic way by using the Cellular Automaton model. Based on the detailed information of individual vehicles of the stochastic traffic flow, the general framework to study Bridge/Traffic/Wind dynamic performance is developed in Chapter 3. Chapter 3 and Chapter 4 also report the results of the bridge's serviceability under normal and extreme loads events, respectively. In Chapter 5, the scenario-based fatigue model is further developed based on the dynamic framework developed in Chapter 3. Finally, the reliability-based analysis is conducted in Chapter 6 to study the fatigue damage caused by the coupling effects among bridge, traffic flow and wind throughout the bridge's service life.
Keywords: reliability; fatigue; equivalent dynamic wheel loading approach; cellular automaton traffic model; bridge/traffic/wind interaction; Long-span bridges -- United States -- Testing; Long-span bridges -- United States -- Design and construction; Long-span bridges -- United States -- Reliability; Safety factor in engineering; Structural control (Engineering)